Gambaran Karakteristik Bidan Dalam Pencegahan Infeksi Masa pandemi Covid-19 di Wilayah Kabupaten Sukoharjo - Fitria Hayu Palupi; Etik Sulistyorini (YCMM, 2022)
During the pandemic, government policies have had an impact on health workers in the prevention of infection and the spread of COVID-19. Midwives as one of the health workers who directly provide health services to pregnant women, during childbirth and the post partum period are the spearhead in breaking the Covid-19 chain. It is undeniable that the practice of independent midwives is the most accessible health service for rural communities. Based on field observation data, there are still discrepancies in the implementation of the Covid 19 Infectious Disease Prevention based on the characteristics of the midwife. Descriptive research design with accidental sampling method on 32 respondents. Characteristics of the majority of respondents aged 41-50 years with the latest education, namely Diploma IV or S1.